Dry root rot disease, an emerging threat to citrus industry worldwide under climate change: A review. (January 2022) - Ezrari, Said; Radouane, Nabil; Tahiri, Abdessalem; El Housni, Zakaria; Mokrini, Fouad; Özer, Göksel; Lazraq, Abderrahim; Belabess, Zineb; Amiri, Said; Lahlali, Rachid
Abstract: Citrus is among the most important fruit crops grown worldwide. Yet, it is known to be affected by many fungal diseases including dry root rot that is becoming a serious threat to citrus plantations worldwide, with an increasing incidence under biotic and/or abiotic stresses. Healthy trees could suddenly wilt and fall with symptoms of root rot, necrotic roots, purple wood discoloration, chlorosis, and dieback until the decline of the tree. Studies have indicated that the disease is caused by a complex of Fusarium spp., which is one of the most diverse fungi species in which Fusarium solani was reported to be the most predominant. More investigations are needed to properly identify pathogens, and understand the conditions and factors associated with dry root rot occurrence. This will help to establish and adopt a solid integrated control strategy for managing this disease. Therefore, this review focuses on symptomology and the recent progress made on morphological and molecular tools employed for accurate identification of the etiological agents associated with dry root rot, and the management strategies developed to control this disease in the recent decades. This review also highlights the new reliable alternative methods used for the control of the disease under sustainable agriculture. Highlights: Researches literature on dry root rot disease of citrus was reviewed and highlighted. Life cycle, symptomology, and the identity of causative agents were reviewed. Morphological and molecular tools for accurate identification of causative agents of DRR were emphasised. Management strategies developed to control this disease in the recent decades were deeply discussed. New reliable alternative methods used for the control of DRR under sustainable agriculture were pointed out.